PENGARUH TERAPI DISTRAKSI AUDIOVISUAL TERHADAP INTENSITAS NYERI PADA PROSEDUR INJEKSI ANAK YANG HOSPITALISASI DI RSU SEMBIRING DELI TUA - Barus, Dewi Tiansa; Purba, Rentawati; Girsang, Rostiodertina; Ginting, Daniel Suranta (Jurnal Penelitian Keperawatan Medik, 2024)
Hospitalization for children can isolate them from the outside world. During treatment, children often display signs of discomfort, such as grimacing, restlessness, fussiness, and lack of cooperation. They may feel fear and anxiety due to new people, unfamiliar environments, and medical procedures. This study aimed to assess the impact of audiovisual distraction therapy on pain levels during injection procedures for children hospitalized at Sembiring Hospital in Deli Tua. The research employed a one-group pre-test post-test design, focusing on an average of 18 children aged 3-6 years each month at the hospital. A total sampling technique was used to select the sample of 18 children. The independent variable was audiovisual distraction therapy, while the dependent variable was the pain experienced during injections. Data were collected through observational methods, and the Wilcoxon statistical test was applied for analysis. Results indicated that prior to the audiovisual distraction, most respondents reported severe pain, with 6 children (33.3%) and 7 children (38.8%) experiencing very severe pain. After the intervention, 6 children (33.3%) reported less pain, while 5 children (27.8%) reported increased pain. The Wilcoxon test yielded a p-value of 0.002, which is less than 0.05, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). The conclusion drawn is that audiovisual distraction therapy significantly reduces pain intensity in hospitalized children during injection procedures at Sembiring Hospital in Deli Tua.